Evaluate

Asked by Rahulsinha1993 | 7th Sep, 2010, 08:50: PM

Expert Answer:

xdx1+sinx= xdx1+sinx.1-sinx1-sinx                    =x(1-sinx)dxcos2x                   = x(sec2x-secxtanx)dxintegrating by parts,                  =x(sec2x-secxtanx)dx-1.(sec2x-secxtanx)dx                = x(tanx-secx) - (tanx-secx)dx +c                = x(tanx-secx)-logsecx+logsecx+tanx +c                =x(tanx-secx)+logsecx+tanxsecx+c                =x(tanx-secx)+log1+sinx+c">

Answered by  | 28th Sep, 2010, 12:56: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.